Harnessing online digital data in biodiversity monitoring - Soriano-Redondo, Andrea; Correia, Ricardo A.; Barve, Vijay; Brooks, Thomas M.; Butchart, Stuart H. M.; Jarić, Ivan; Kulkarni, Ritwik; Ladle, Richard J.; Vaz, Ana Sofia; Di Minin, Enrico (Public Library of Science, 2025)
Online digital data from media platforms have the potential to complement biodiversity monitoring efforts. We propose a strategy for integrating these data into current biodiversity datasets in light of the Kunming-Montreal Global Biodiversity Framework.